PENGARUH TINGKAT LIKUIDITAS, AKTIVITAS dan SOLVABILITAS dalam MEMPREDIKSI LABA PERUSAHAAN - Wasi Widayadi; Irma Sari Permata; Mulyadi (Universitas Lambung Mangkurat, 2019)
Good corporate financial performance is an important aspect that provides an overview of the financial health conditions of the company and management and investors can find out whether or not the company's health conditions are good. The company's financial performance can be known by using financial ratio analysis, including liquidity ratios, activity, solvency, profitability and market ratios. Based on the description above it is very interesting to examine the influence of the level of liquidity, activity and solvency in predicting corporate profits. The main objective of this research is to examine 3 financial ratios, namely liquidity ratios, activity ratios and solvency ratios to corporate profits. The sample of this study were 5 cosmetic industry companies with panel data from 2011 to 2017. The method used was quantitative research method based on secondary data in the form of annual financial reports on cosmetics and household goods manufacturing companies listed on the Stock Exchange Indonesia.